A Mechanical Comparison of the Compressive Force Generated by Various Headless Compression Screws and the Impact of Fracture Gap Size. (September 2021) - Ilyas, Asif M.; Mahoney, Jonathan M.; Bucklen, Brandon S.
Background: There is evidence that interfragmentary fracture gap size may affect the compression achievable with a modern headless compression screw (HCS). This mechanical study compared the compression achieved by 3 commercial HCS systems through various fracture gaps: CAPTIVATE Headless (Globus Medical, Inc, Audubon, Pennsylvania), Synthes (DePuy Synthes, Westchester, Pennsylvania), and Acumed Acutrak 2 (Acumed LLC, Hillsboro, Oregon).Methods: Screws were inserted into a custom test fixture composed of polyurethane synthetic bone foam fragments, separated by a layer of easily compressible polyurethane foam simulating a fracture gap. Compression was measured after final insertion and countersinking. The effect of the interfragmentary fracture gap size on the compression generated was also investigated.Results: The CAPTIVATE Headless 3.0 mm screw (70.1 ± 5.7 N) and the Synthes 3.0 mm screw (64.9 ± 7.3 N) achieved similar compressive forces after final countersink. Similar comparisons were found for the CAPTIVATE Headless 2.5 mm and Synthes 2.4 mm screws, and the CAPTIVATE Headless 4.0 mm and Acutrak 2 Standard screws. The final compression of the CAPTIVATE Headless 2.5 mm and Synthes 2.4 mm screws was not significantly affected when the fracture gap was doubled from 2 to 4 mm, but was reduced significantly by 95.9% with the Acutrak 2 Micro screw.Conclusion: When comparing like-sized screws, the CAPTIVATE, Synthes, and Acutrak 2 HCS systems demonstrated similar potential compressive forces. However, compared with the CAPTIVATE Headless and Synthes HCS systems, which are inserted with a compression sleeve that is not gap distance–dependent, the Acutrak 2 HCS system demonstrated less compression when the simulated fracture gap size was increased to 4 mm.